Smart Arm Robot using Visual Basic program - Wee Joo Ann (Universiti Malaysia Perlis, 2008)
The aim of the project was to design the software using Visual Basic program to control the robot arm, design the electronic circuit and build the Robot Arm. The controlling of the robot arm using wireless radio frequency technology with the distance of 20metre from the controller; the robot is able to move forward, backward, left, right, rotate 350 degree, and the entire arm with gripper can move easily when using wireless controller. Beside that, the robot has a gripper that can grip the object that is hard and dangerous cannot be handling by human being likes chemical or radioactive materials. User can control the robot by press the certain key from computer keyboard, then the signal will connect to parallel port (Printer port) on computer, before the signal transmit by transmitter, the (Digital to analog converter circuit) is used to convert the digital signal from computer to analog signal before transmit by transmitter. When the signal is received by Receiver Circuit, the signal will operate the Relay Circuit and then the signal is connected to the Motor Control Circuit to control the speed of the motor (movement of the robot and ability the arm to grip the item).